Elevation of glycoprotein nonmetastatic melanoma protein B in type 1 Gaucher disease patients and mouse models. Issue 9 (30th July 2016) - Kramer, Gertjan; Wegdam, Wouter; Donker‐Koopman, Wilma; Ottenhoff, Roelof; Gaspar, Paulo; Verhoek, Marri; Nelson, Jessica; Gabriel, Tanit; Kallemeijn, Wouter; Boot, Rolf G.; Laman, Jon D.; Vissers, Johannes P.C.; et al.
Abstract : Gaucher disease is caused by inherited deficiency of lysosomal glucocerebrosidase. Proteome analysis of laser‐dissected splenic Gaucher cells revealed increased amounts of glycoprotein nonmetastatic melanoma protein B (gpNMB). Plasma gpNMB was also elevated, correlating with chitotriosidase and CCL18, which are established markers for human Gaucher cells. In Gaucher mice, gpNMB is also produced by Gaucher cells. Correction of glucocerebrosidase deficiency in mice by gene transfer or pharmacological substrate reduction reverses gpNMB abnormalities. In conclusion, gpNMB acts as a marker for glucosylceramide‐laden macrophages in man and mouse and gpNMB should be considered as candidate biomarker for Gaucher disease in treatment monitoring. Abstract : Gaucher disease (GD) is caused by an inherited deficiency of lysosomal glucocerebrosidase (GBA1), leading to endo‐lysosomal glucosylceramide (GlcCer) accumulation, causing endo‐lysosomal stress. This drives glycoprotein nonmetastatic melanoma protein B (gpNMB) induction in macrophages (Gaucher cells), which is shed and enters the circulation of both GD mice and patients. gpNMB goes down upon therapeutic intervention, and should be viewed as candidate biomarker for Gaucher disease.